Elevated Cortisol Leaves Working Memory Unaffected in Both Men and Women - Human, Robyn; Henry, Michelle; Jacobs, W. Jake; Thomas, Kevin G. F. (Frontiers in Human Neuroscience, 2018)
Hypothalamic-pituitary-adrenal (HPA) axis activation following stress exposure leads to the release of cortisol into the bloodstream and, ultimately, to altered neural functioning in particular brain regions (e.g., the prefrontal cortex (PFC)). Although previous studies suggest that exposure to acute psychosocial stress enhances male performance on PFC-based working memory (WM) tasks, few studies have adequately investigated female performance on WM tasks under stressful conditions. Hence, we compared associations between elevated (relative to baseline) levels of circulating cortisol and n-back performance in a South African sample (38 women in the late luteal phase of their menstrual cycle, 38 men). On Day 1, participants completed practice n-back tasks. On Day 2, some completed the Trier Social Stress Test, whereas others experienced a relaxation period, before completing 1-back and 3-back tasks. We measured self-reported anxiety and salivary cortisol at baseline, post-manipulation, and end of session. We reconstituted group assignment so that all women with elevated cortisol were in one group (EC-Women; n = 17), all men with elevated cortisol were in another (EC-Men; n = 19), all women without elevated cortisol were in a third (NoEC-Women; n = 21), and all men without elevated cortisol were in a fourth (NoEC-Men; n = 19). Analyses suggested this reconstitution was effective: In EC, but not NoEC, groups cortisol levels rose significantly from baseline to post-manipulation. Analyses of n-back data detected significant relations to task load (i.e., better performance on 1-back than on 3-back tasks), but no significant relations to sex, performance accuracy/speed, or cortisol variation. The data patterns are inconsistent with reports describing sex differences in effects of stress on WM performance. We speculate that cross-study methodological differences account for these inconsistencies, and, particularly, that between-study variation in the magnitude of baseline cortisol levels might affect outcomes. For instance, diurnal cortisol rhythms of South African samples might have flatter curves, and lower baseline values, than predominantly Caucasian samples from the United States and western Europe due to greater prenatal and lifetime stress, more socioeconomic disadvantage, and faster ancestral life history strategies. We describe ways to disconfirm this hypothesis, and urge further cross-national research exploring these possibilities.